Can individual, dyadic, or collaborative planning reduce sedentary behavior? A randomized controlled trial. (October 2021) - Szczuka, Zofia; Kulis, Ewa; Boberska, Monika; Banik, Anna; Kruk, Magdalena; Keller, Jan; Knoll, Nina; Scholz, Urte; Abraham, Charles; Luszczynska, Aleksandra
Abstract: Rationale: Although effects of individual planning interventions on physical activity (PA) are well established, less is known about the relationships between planning and sedentary behavior (SB). Objective: This study evaluated the efficacy of individual planning, dyadic planning (i.e., joint planning, targeting the behavior of one person only: the target person), and collaborative planning (i.e., joint planning and joint behavioral performance) on sedentary behavior among dyads. Methods: Dyads ( N = 320 target persons and their partners, aged 18–90 years) were randomized into three PA planning conditions (individual, dyadic, or collaborative) or an active (education) control condition. Main outcomes, i.e., sedentary time, proportion of time spent in SB and light-intensity PA, proportion of time spent in SB and total PA were measured with GT3X-BT accelerometers at baseline, 1-week follow-up, and 36-week follow-up. Two-level models with measurement points nested in participants were fit, separately for target persons and partners. Results: Findings for target persons obtained at 1-week follow-up indicated that in the collaborative planning condition SB time significantly decreased, compared to the control condition ( p = .013). There was an improvement in the proportion of time spent in SB and light-intensity PA ( p = .019), and the proportion of time spent in SB and total PA ( p = .018), indicating that SB time was displaced by PA. Effects of individual and dyadic planning were not significant, compared to the control condition. None of interventions had a significant effect on SB indices at 36-week follow-up. Regarding dyadic partners, there were no effects of planning interventions at 1-week follow-up or 36-week follow-up, compared to the control condition. Conclusions: Collaborative planning may prompt a short-term reduction of SB time and result in a shift towards a healthier balance between SB time and PA time among target persons, who did not adhere to PA guidelines at baseline. Highlights: Physical activity planning may help to reduce time spent on sedentary behavior. Collaborative planning reduced sedentary time (measured with accelerometers). Effects were observed among target persons, but not among their planning partners. Short term (1-week) effects were found, but no long-term effects were observed. Individual and dyadic planning did not influence sedentary time.